State of the Art in Nano-Bioimaging 2018
DOI: 10.5772/intechopen.72841
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Magic Sized Quantum Dots: Luminescent Markers and Probes

Abstract: Nanoscience and nanobiotechnology have aroused great academic and technological interest. Works relating biomaterials at the nanoscale can reach new biotechnologies and help in the development and use of tools for bioimage and diagnosis applications. In this work we demonstrated the advantages of magic sized quantum dots as luminescent markers and probes to bioimage applications. The visualization of MSQDs bioconjugated with biological probes in cells were performed at periods greater than 2 h, and visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Bioimaging assays are biological applications QDs since they can be bioconjugated with proteins, antibodies, and DNA. [39,48,49]. In general, these tests depend on the biocompatibility of QDs, which is obtained by functionalizing the surface of these nanoparticles.…”
Section: Nanocrystals As Luminescent Markers (Nanomarkers)mentioning
confidence: 99%
See 2 more Smart Citations
“…Bioimaging assays are biological applications QDs since they can be bioconjugated with proteins, antibodies, and DNA. [39,48,49]. In general, these tests depend on the biocompatibility of QDs, which is obtained by functionalizing the surface of these nanoparticles.…”
Section: Nanocrystals As Luminescent Markers (Nanomarkers)mentioning
confidence: 99%
“…[56] The tracking and study of biomolecules labeled with QDs in vitro and in vivo is a reality in several areas, allowing us to analyze the location and distribution of bioconjugate in biological systems. Silva et al demonstrated that the CdSe/ CdS MSQDs could be bioconjugated with several biomolecules aiming at the most diverse luminescent probes [38][39][40][41][42] in biosensors. [43,44] Dias et al labeled a phospholipase A2 isolated from Bothrops alternatus snake venom with CdSe/CdS MSQDs to track it in myoblast culture, making it possible to identify the bioconjugate on the surface of the plasma membrane and in the nuclear region.…”
Section: Nanocrystals As Luminescent Markers (Nanomarkers)mentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make quantum dots an excellent tool, which is very important in bioimaging and photonic applications. 12,13 Another type of interesting QD is the ultrasmall QDs (USQDs), which have sizes smaller than 5 nm and are rarely reported in the literature. In order to improve the biocompatibility and luminescence intensity, CdSe USQDs have been coated with a CdS shell, forming core/shell type structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Quantum dots (QDs) are known to have excellent absorption and emission properties that can be adjusted by varying the size. These properties make quantum dots an excellent tool, which is very important in bioimaging and photonic applications. , Another type of interesting QD is the ultrasmall QDs (USQDs), which have sizes smaller than 5 nm and are rarely reported in the literature. In order to improve the biocompatibility and luminescence intensity, CdSe USQDs have been coated with a CdS shell, forming core/shell type structure. Core/shell semiconductor heterostructures have new and interesting optical properties that can be manipulated in the function of core- or shell-type material.…”
Section: Introductionmentioning
confidence: 99%